THE APPROACHES AND TECHNIQUES OF AUDIOLINGUAL AND DIRECT METHOD - DJABBOROVA , Nodira (Journal of Pedagogical and Psychological Studies, 2023)
Audiolingual Method (ALM) of the late 1940 and 1950s is considered as one of the best examples of periodical method. The ALM with its oral production drills is used almost half a century. Whereas, Direct Method started from behavioral theories of learning of the time. The approaches and techniques in the language teaching profession have stressed the importance of self – esteem, motivation, students cooperatively learning together, developing individual strategies for constructing meaning focused on the communicative process in language learning. Keep on reading for all the details it is essential to know about the most popular foreign language teaching methods. Some of the ones covered are the communicative approach, total physical response, the direct method, task-based language learning, suggestopedia, grammar-translation, the audio-lingual approach and more.